Utilization of carbon dioxide using electrochemical reduction: A review - Al-Shamari, Mansoor (2024)
This article explores the electro-chemical Carbon dioxide Reduction Cell (eCO2RC), delving into fundamental principles, methods, applications, and the latest approaches for converting CO2 emissions into valuable products. Product outcomes depend on electron exchange and electrode surface attributes used in the CO2 reduction. The study focuses on C1 and C2 products, emphasizing the necessity for selective materials and catalysts to enhance product recovery while minimizing energy consumption. Converting eCO2 into valuable products is seen as a crucial method for transforming waste into value, addressing the challenge of mitigating global warming through gas emission reduction.